2022
DOI: 10.4274/tjo.galenos.2021.46588
|View full text |Cite
|
Sign up to set email alerts
|

Ophthalmologic Manifestations in Autism Spectrum Disorder

Abstract: Objectives: The purpose of this study was to describe the ophthalmologic manifestations found in patients with autism spectrum disorder (ASD) and to assess their prevalence in the different types of ASD. Materials and Methods: This prospective observational study included 344 patients with ASD seen over a period of 8.5 years. They were classified into four subgroups (autism, Asperger syndrome, pervasive developmental disorders not otherwise specified [PDD-NOS], and othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…The preponderance of visual phenotypes over acoustic in these mutants for ASD risk genes was not observed in a previous larger screen of zebrafish lines for schizophrenia-associated genes ( 17 ). It is possible that the distinct behavioral patterns of genes in different mutant groups reflect meaningful pathophysiology, as problems with the visual system have been reported in up to 50% of people with ASD ( 45 , 46 ).…”
Section: Resultsmentioning
confidence: 99%
“…The preponderance of visual phenotypes over acoustic in these mutants for ASD risk genes was not observed in a previous larger screen of zebrafish lines for schizophrenia-associated genes ( 17 ). It is possible that the distinct behavioral patterns of genes in different mutant groups reflect meaningful pathophysiology, as problems with the visual system have been reported in up to 50% of people with ASD ( 45 , 46 ).…”
Section: Resultsmentioning
confidence: 99%
“…Another 10-year-old case of ASD reported loss of vision due to punctate Ö. Ö. ÖZCAN, İ. ŞAHBAZ, E. TAŞDÖNDÜREN, M. KARAHAN epithelial erosions, corneal and conjunctival keratinization 52 . Gutierrez et al reported that amblyopia, strabismus, optic neuropathy, refractive errors and ocular motility disorders are common in patients with ASD especially in pediatric population 53 but the ophthalmic examination of ASD has still major deficiencies in the literature. In particular, pupil and corneal studies can provide important information about ASD symptoms and biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…Opthomological differences exist in those with ASD versus controls. 33,34 Such data were not available in this study. As mentioned in 2.2 above the drawings were simple and not small, and all participants wearing glasses kept them on, and they were asked if they could see the pictures clearly.…”
Section: Confoundersmentioning
confidence: 96%